THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF EARLY BREASTFEEDING INITIATION (IMD) IN CAESAREAN SECTION DELIVERY AND COLOSTRUM PRODUCTION - Desi Andrawati; Dwi Estuning Rahayu; L.A Wijayanti; Koekoeh (Universitas STRADA Indonesia, 2025)
One cause of colostrum discharge in caesarean section delivery is the implementation of early initiation of breastfeeding (IMD). The study's objective was to investigate the relationship between the implementation of IMD caesarean section delivery and colostrum discharge. The study design was cross-sectional , the population was 50 mothers who underwent caesarean section delivery , sampling using systematic sampling techniques , the number of respondents was 34 people according to the inclusion criteria. The research instruments were questionnaires and observations, then analyzed using Chi-square correlation. and it was found that χ2 count was 5.37 , with a p-value of 0.02 (<0.05), a moderate relationship of 0.37. It was found that the implementation of I MD with an optimal duration (more than 60 minutes) in caesarean section delivery can play a role in accelerating the release of colostrum (less than 24 hours).